2012
DOI: 10.1115/1.4007345
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fuel Composition Effects on Flashback Using a Confined Jet Flame Burner

Abstract: Flashback is the main operability issue associated with converting lean, premixed combustion systems from operation on natural gas to operation on high hydrogen content fuels. Most syngas fuels contain some amount of hydrogen (15-100%) depending on the fuel processing scheme. With this variability in the composition of syngas, the question of how fuel composition impacts flashback propensity arises. To address this question, a jet burner configuration was used to develop systematic data for a wide range of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…In most of UCI's previous work, a quartz enclosure was used as a strategy to stabilize the flame on top of the burner tube [23]. In most of UCI's previous work, a quartz enclosure was used as a strategy to stabilize the flame on top of the burner tube [23].…”
Section: Parameters Studiedmentioning
confidence: 99%
See 3 more Smart Citations
“…In most of UCI's previous work, a quartz enclosure was used as a strategy to stabilize the flame on top of the burner tube [23]. In most of UCI's previous work, a quartz enclosure was used as a strategy to stabilize the flame on top of the burner tube [23].…”
Section: Parameters Studiedmentioning
confidence: 99%
“…This unique method was introduced to simulate a typical practical gas turbine control strategy [23]. The AFT is held constant in each EB experiment.…”
Section: Protocol I: Constant Adiabatic Flame Temperature (Aft)mentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors [8][9][10] stated that the behaviour of fuel mixture can be significantly different than that of individual constituents. Syred et al 11,17 showed considerable difference in flashback blowoff limits when increasing the hydrogen content of the fuel, whilst demonstrating that these limits could be correlated with the inlet tangential velocity level..…”
Section: Introductionmentioning
confidence: 99%